IDENTIFIKASI PENGGUNAAN MEDIA SOSIAL DAN DAMPAKNYA PADA KINERJA PEMASARAN DALAM PERSPEKTIF EKONOMI ISLAM PADA USAHA SKALA MIKRO DI KABUPATEN BANYUMAS - sulasih, sulasih; Wahyuningtyas, Ida Puspitarini; Rohiwan, Sidik; Suliyanto, Suliyanto (MUSLIM HERITAGE, 2024)
AbstractThis research aims to determine the role of entrepreneurial orientation on the use of social media and marketing performance with innovative ability as a moderating variable in microscale businesses in Banyumas Regency. The sample in this study was determined using slovin and sampling using the purposive sampling method and the sample size was 100 respondents. The data analysis technique used in this research is partial least squares (PLS) analysis. The research results show that it partially has a positive and significant effect, while the use of social media partially mediates the effect of entrepreneurial orientation on marketing performance. Mediation in this research model is partial, in other words, the use of social media has a function to bridge the influence of entrepreneurial orientation on marketing performance. However, because the mediation characteristics are partial, even without the social media use variable, entrepreneurial orientation is still able to influence marketing performance positively and significantly. These results confirm that entrepreneurial orientation can increase and strengthen the use of social media by micro-scale business actors in Banyumas, which will also have an impact on improving business performance. Furthermore, innovative ability does not moderate the relationship between the use of social media and marketing performance. Entrepreneurial orientation, innovative ability and the use of social media by micro-scale business actors in Banyumas Regency are in accordance with the Islamic economic perspective where business actors dare to take risks, are innovative and use media. in the form of technology for muamalah activities that are in accordance with sharia principles, and this has an impact on the benefit of the people in the form of increasing marketing performance AbstrakPenelitian ini bertujuan untuk mengetahui peran orientasi kewirausahaan pada penggunaan media sosial dan kinerja pemasaran dengan kemampuan inovatif sebagai variabel moderasi pada usaha skala mikro di Kabupaten Banyumas. Sampel dalam penelitian ini ditentukan dengan menggunakan slovin dan pengambilan sample dengan metode purposive sampling dan jumlah sampel sebanyak 100 responden. Teknik analisis data yang digunakan dalam hal ini penelitian adalah analisis partial least square (PLS). Hasil penelitian menunjukkan bahwa secara partial berpengaruh positif dan signifikan, sedangkan penggunaan media sosial memediasi secara partial pengaruh orientasi kewirausahaan pada kinerja pemasaran. Mediasi dalam model penelitian ini bersifat parsial, dengan kata lain, penggunaan media sosial memiliki fungsi untuk menjembatani pengaruh orientasi kewirausahaan terhadap kinerja pemasaran. Namun, karena karakteristik mediasinya partial, bahkan tanpa variabel penggunaan media sosial, orientasi kewirausahaan masih mampu mempengaruhi kinerja pemasaran secara positif dan signifikan. Hasil ini menegaskan bahwa orientasi kewirausahaan dapat meningkatkan dan memperkuat penggunaan media sosial oleh para pelaku usaha skala mikro di Banyumas, yang juga akan berdampak pada peningkatan kinerja bisnis. Lebih lanjut, kemampuan inovatif tidak memoderasi antara penggunaan media sosial dengan kinerja pemasaran, Orientasi kewirausahaan, kemampuan inovatif dan penggunaan media sosial oleh pelaku usaha skala mikro di Kabupaten Banyumas telah sesuai dengan perspektif ekonomi islam dimana pelaku usaha berani mengambil resiko, memiliki inovatif serta menggunakan media berupa teknologi untuk kegiatan muamalah yang sesuai dengan prinsipprinsip syariah, dan hal tersebut berdampak pada kemaslahatan umat berupa adanya peningkatan kinerja pemasaran.